A notion of enterprise risk management : enhancing strategies and wellbeing programs - Majumder, Soumi; Dey, Nilanjan (Emerald Publishing Limited, 2024)
In today's dynamic business landscape, the effective management of risk is paramount to the success and resilience of any organization. A Notion of Enterprise Risk Management presents a comprehensive exploration of practices, policies, and frameworks that enable businesses to navigate a myriad of risks. Contributions from a global team of authors provides a range of insights on Enterprise Risk Management (ERM) and its pivotal role in safeguarding organizations against potential hazards. Drawing on contemporary research, it addresses the unique challenges posed by Industry 4.0, exploring the intersection of risks and cultural shifts within the business landscape. Key topics include the transformative potential of machine learning; big data; and IoT in the domain of enterprise risk management. With its comprehensive coverage and diverse perspectives, A Notion of Enterprise Risk Management is an indispensable resource for individuals involved in any form of risk management. Whether you are an academic researcher, a seasoned practitioner, or a policymaker, this book will equip you with the knowledge and tools necessary to navigate the complexities of enterprise risk management.
Keywords: Entrepreneurship.; Risk management.; Business & Economics -- Finance -- Financial Risk Management.; Entrepreneurship, Start-ups.; Finance and the finance industry.; Risk assessment.; elektronické knihy; electronic books